A triarterial arcade - the radial - median - ulnar type of superficial palmar arch - Bovindala Bhagyalakshmi; Challa Ratna Prabha; Gullapalli Aparna; Madabhushi Chandramohan (Wolters Kluwer Medknow Publications, 2014)
The most essential prerequisite for hand surgeons is a comprehensive knowledge of variations in the arterial architecture of the hand. There are two well designed arterial arches, superficial palmar arch (SPA) and the deep palmar arch (DPA) situated superficial and deep to flexor tendons and lumbrical muscles respectively. Even though both are formed by the contribution of radial and ulnar arteries, variations are numerous and frequent in SPA that attracts the attention of surgeons. During the routine dissections we found a rare variation in the structural architecture of SPA which was formed by anastomosis of the radial - median and ulnar arteries. This triarterial combination of SPA is an advantage in reconstructive hand surgeries, microvascular surgeries and radial artery harvesting for Coronary artery bypass graft. Presence of incomplete SPA is dangerous to tackle surgically. Screening is essential to know the exact arterial pattern for successful hand surgeries without postoperative complications.